THE IMPACT OF ARTIFICIAL INTELLIGENCE IN EDUCATION ON STUDENT LEARNING - Bakhromova Gulsanam Yunusbek kizi; Norimboyeva Mukhlisa Shodiboy kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article analyzes how Artificial Intelligence affects student learning outcomes. It shows that AI enhances achievement, engagement, and efficiency through personalized learning, while also raising concerns about over-reliance, ethics, and unequal access in education.